The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1103/physrevlett.111.225001
|View full text |Cite
|
Sign up to set email alerts
|

Strongly Reduced Penetration of Atomic Deuterium in Radiation-Damaged Tungsten

Abstract: Link to publication Citation for published version (APA):'t Hoen, M. H.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…On the other hand, experimental results 37 suggest that for ion energy below 5 eV/H, typical of detached plasma as the one treated in the previous section, the surface process can be important and limits the uptake of hydrogen, i.e. the adsorption on the surface and the further absorption from surface to bulk could be the limiting process for the growth of during such exposure.…”
Section: Resultsmentioning
confidence: 92%
“…On the other hand, experimental results 37 suggest that for ion energy below 5 eV/H, typical of detached plasma as the one treated in the previous section, the surface process can be important and limits the uptake of hydrogen, i.e. the adsorption on the surface and the further absorption from surface to bulk could be the limiting process for the growth of during such exposure.…”
Section: Resultsmentioning
confidence: 92%
“…This requires a special detector geometry with normal incidence and grazing exit angle, resulting in reaction angles close to 100 • [1]. The analyzed depth, however, is limited to a near surface layer of several hundred nanometers: For many applications, such as the study of hydrogen isotope diffusion in metals [7] [8] or the determination of the amount of trapped deuterium in wall materials of nuclear fusion experiments [9], this shallow analyzed depth range is largely insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…Two different damage doses of 1 and 10 dpa were obtained using implantation fluences of 2.88 × 10 14 and 2.88 × 10 15 ions/cm 2 under an ion flux of approximately 2 × 10 12 ions/cm 2 s –1 . The ion fluence to damage dose conversion was done by using the SRIM (Stopping and Range of Ions in Matter) 2013 Monte Carlo code ( 36 ) with the full cascade mode using the threshold W displacement energy of 90 eV ( 37 ). The displacement levels quoted here do not represent the final damage to W since thermal effects are not considered in the SRIM calculations, which, however, does not affect our study reported here.…”
Section: Methodsmentioning
confidence: 99%